PERCEPTION REGARDING SELF-MEDICATION OF ANTIBIOTICS IN GENERAL PUBLIC SECTOR UNIVERSITY OF SOUTHERN PUNJAB: A COMPARISON BETWEEN MEDICAL AND NON-MEDICAL STUDENTS - Khalid, S; Ali, Q; Hafeez, MM; Malik, A (Biological and Clinical Sciences Research Journal, 2021)
Self-medication with antibiotics is a most rapidly emerging problem especially in developing countries like Pakistan. Antibiotics are easily accessible to the general public without consulting any practitioner even without prescriptions. So there are many risks linked to the inappropriate use of antibiotics. The main aim of this study was to assess the wrong practice of self-medication in public sector universities of southern Punjab. The current study also compares the self-medication practices in various departments of universities. A validated questionnaire was used to collect data. Descriptive statistics were used to analyze the data and inferential statistics (chi-square test). The study was included data from 900 students including both males and females from various departments. Among 900 students, 450 students of medical while 450 were non-medical students. Frequency of self-medication was found to 57 %. The antibiotics more frequently use for self-medication were Augmentin (37 %), Amoxicillin (23 %). Fever and cough were the most frequent indication for the use of self-medicated antibiotics. Because of their sufficient knowledge of pharmacology, most students were self-medicated (40%). Academic knowledge is the principal source of antibiotic information (60%). Just (39%) of the students thought that self-medication is part of the self-core, 31% of the students perceived that the availability of non-prescription drugs could prevent the growing trend of self-medication with antibiotics. 30% of students perceived that antibiotics were aware of the harms of self-medication or informed about them. Based on this study, it can be concluded that a high proportion of medical students and non-medical students use antibiotics without medical prescription and such practices are more common in the general public sector.